Austenite formation kinetics from multicomponent cementite-ferrite aggregates. (1st September 2020) - Wu, Y.X.; Wang, L.Y.; Sun, W.W.; Styles, M.J.; Studer, A.J.; Bréchet, Y.; Arlazarov, A.; Hutchinson, C.R.
Abstract: Metastable austenite strongly influences the mechanical properties of many advanced high strength steels (AHSS) and its formation kinetics during intercritical annealing strongly depend on the initial microstructure. In this contribution, we have performed detailed kinetic studies of austenite formation from cementite-ferrite aggregate in a range of Fe-C-Mn and Fe-C-Mn-Si/Al alloys via in situ neutron powder diffraction. Depending on the relative contribution of cementite dissolution in respect to migrating interface of austenite/ferrite, the incomplete dissolution of enveloped cementite limited by slow diffusion in austenite could result in austenite plateauing below equilibrium, while fast dissolution of matrix cementite could result in austenite plateau above equilibrium. Both contributions need to be considered and modelled to describe the austenite formation kinetics. Graphical abstract: Image, graphical abstract